Experiences of Cooperating Teachers on Teaching Practice Supervision in Eswatini, Swaziland - Alfred F. Tsikati; Khomb’sile N. Dlamini (Journal of International Agricultural and Extension Education, 2019)
Cooperating teachers (CTs) are key participants in ensuring a valuable experience for the student teacher (ST) during teaching practice. Surprisingly, their voices largely remain absent in the extant literature. Thus, the purpose of the study was to investigate the experiences of CTs during teaching practice supervision in Eswatini. A descriptive research design using a census of 46 CTs for student teachers (STs) who did teaching practice in the 2015/16 academic year of the University of Eswatini in the Department of Agricultural Education was used. A selfadministered questionnaire was used for collecting data. A five-point numerical scale and sixpoint Likert-type rating scale were used to measure the variables. Three lecturers from the Department of Agricultural Education and Extension and two agriculture teachers established content and face validity for the questionnaire. Inter-item reliability from a pilot study was .78. Findings of the study revealed that CTs were supported by the University through the supervisors and Teaching Practice Handbook. The CTs noted that establishing rapport with the STs was essential and head teachers needed to visit the STs in the respective classes they teach. STs were good in developing, organizing and using instructional materials but had challenges in disciplining learners. The study recommended that CTs should be provided with trainings and incentives so that they can effectively discharge their duties during teaching practice.
Keywords: cooperating teachers; in-service teachers; student teachers; teaching practice; teaching practicum